ANALISIS FAKTOR YANG BERPENGARUH TERHADAP PEMBENGKAKAN BIAYA SELAMA PELAKSANAAN PROYEK DI MASA PANDEMI COVID-19 PADA PELAKU JASA KONSTRUKSI SKALA KECIL DI BALI - Ida Ayu Cri Vinantya Laksmi; I Wayan Jawat; Ni Komang Armaeni (Jurusan Teknik Sipil Universitas Bangka Belitung, 2021)
The Covid-19 virus pandemic that hit Indonesia, especially Bali, had a huge impact on people's lives. This has an impact on several sectors, ranging from the health sector, the economy, education, tourism, including the development sector. The Corona outbreak has forced all countries to revise the development plans that have been proclaimed. Targets were realistically adjusted, assumptions were changed according to current circumstances, and short-term program priorities were shifted largely to address the Covid-19 pandemic. In the context of accelerating development to restore economic conditions, several small-scale construction service actors are still able to carry out development even though they have to experience several obstacles. During the implementation of development during a pandemic, of course, some costs undergo significant changes that can even cause cost overruns. The swelling of construction project costs is highly dependent on several factors, both internal and external factors of the project. Several factors were very influential in cost overruns during the implementation of projects carried out by small-scale construction service actors during the Covid-19 pandemic, including inaccurate cost estimates (9.33%), errors in choosing work methods (8.84%) ), low labor productivity (8.15%), dimensional error/measurement of work in progress (8.14%), frequent work delays (8.04%), schedule delays due to weather effects (8.00%), an increase in material prices (7.94%), high equipment prices/rents (7.67%), delays/lack of materials and materials (7.31%), material damage (6.81%), material specifications required unsuitable (6.52%), and untimely payment methods (6.26%).